"Arreda (Get Away), Man, Here Comes Woman": Gender and Afro-religiosity in Afro-Brazilian Religious Organizations - Moura, Renan Gomes de; Nascimento Prevot, Rejane (Organizações & Sociedade, 2022)
This research investigates how religious organizations of the African matrix, through the discourse expressed in the songs intended for and chanted to the Pomba-Giras, contest gender stereotypes, enabling the understanding of multiple femininities. In this article, to analyze the corpus, we opted for the methodological theoretical contribution of the French discourse analysis (DA) derived from Pêcheux. We observed that by studying gender in religious organizations, through the figure of the Pomba-Giras, spaces are opened up for new dialogues within the field of organizational studies, besides understanding how some words used in daily life to belittle women can assume other meanings in the songs, contributing to an understanding of the performance of femininity in a non-puritanical way. Based on the reflection proposed by this article, we dare to affirm that the Pomba-Giras is not only a deity, but also one of the numerous modes of gender performance, serving as a lens to understand other forms of resistance and existence of the multiple femininities in various types of organizations and organizational practices. Following Oyěwùmí in proposing an Oxunist analysis of gender and based on the characteristics of the divinity Ọ̀ṣun (Oxum), we suggest pombagirismo here as an analytical orientation for gender studies.